La playa de los ahogados - Villar, Domingo (Nuevos tiempos (Madrid, Spain), 2010)
One misty autumn dawn, in a quiet fishing port in northwest Spain, the body of a sailor washes up in the harbor. Detective Inspector Leo Caldas is called in from police headquarters in the nearby city of Vigo to sign off on what appears to be a suicide; but details soon come to light that turn this routine matter into a complex murder investigation. Finding out the truth is not easy when the villagers are so suspicious of outsiders. As Caldas delves into the maritime life of the village, he uncovers a disturbing decade-old case of a shipwreck and two mysterious disappearances. This chilling story of violence, blackmail, and revenge has enthralled readers across Europe.